Zmienność wybranych zdolności motorycznych pod wpływem ukierunkowanego szkolenia uczniów klas mundurowych - Tłuczek, Waldemar (Uniwersytet Rzeszowski, 2026)
Celem pracy była ocena zmian wybranych zdolności motorycznych uczniów klas mundurowych w wyniku systematycznego i ukierunkowanego szkolenia realizowanego w programie Oddziałów Przygotowania Wojskowego (OPW). Badanie miało wykazać, w jakim stopniu roczny cykl szkoleniowy wpływa na rozwój sprawności fizycznej oraz zdolności istotnych dla dalszej służby mundurowej. W badaniu uczestniczyło 56 uczniów, w tym 31 mężczyzn i 25 kobiet w wieku 16-17 lat. Pomiary przeprowadzono trzykrotnie w trakcie roku szkoleniowego, co pozwoliło uchwycić kierunek i tempo zmian. Do oceny wykorzystano pomiary budowy i składu ciała, test Coopera, testy siły eksplozywnej (SJ, CMJ), pomiar siły izometrycznej dłoni, testy zwinności oraz próby równowagi na platformie stabilometrycznej. Zastosowane metody umożliwiły pełną ocenę wpływu programu szkoleniowego na funkcjonowanie motoryczne uczestników. Wyniki badań jednoznacznie wskazują na bardzo korzystny wpływ szkolenia OPW. Zaobserwowano znaczną poprawę w kluczowych zdolnościach motorycznych, szczególnie w wytrzymałości tlenowej, sile eksplozywnej, sile izometrycznej dłoni i ogólnej prawności fizycznej. U większości uczniów odnotowano także korzystne zmiany w składzie ciała, takie jak wzrost masy mięśniowej oraz zmniejszenie udziału tkanki tłuszczowej, zwłaszcza u mężczyzn. Kobiety natomiast wykazywały bardzo dobre postępy w zakresie koordynacji i równowagi, co również potwierdza skuteczność programu. Największą dynamikę poprawy zanotowano między pierwszym a drugim pomiarem, co świadczy o silnej adaptacji organizmu do intensywnego treningu. Końcowy pomiar potwierdził stabilizację wzrostów, przy utrzymaniu wysokiego poziomu sprawności. Podsumowując, ukierunkowane szkolenie w klasach mundurowych skutecznie rozwija zdolności motoryczne uczniów i może być traktowane jako wartościowy model przygotowania fizycznego. Uzyskane wyniki stanowią mocny argument za dalszym rozwojem i doskonaleniem programów OPW oraz ich wykorzystaniem w procesie rekrutacji i szkolenia kandydatów do służb mundurowych.

The aim of this study was to evaluate changes in selected motor abilities of students enrolled in uniformed classes as a result of systematic and targeted training implemented within the Military Preparation Unit (OPW) program. The study sought to determine the extent to which a one-year training cycle influences the development of physical fitness and abilities essential for future service in uniformed forces. A total of 56 students participated in the study, comprising 31 males and 25 females aged 16-17. Measurements were conducted at three points over the course of the training year, which allowed for the identification of toth the direction and the rate of observed changes. The assessment protocol encompassed a comprehensive battery of measurements, including body composition and morphological indices, the Cooper aerobic endurance test, explosive lower-limb power evaluations (squat jump and countermovement jump), isometric handgrip strength testing, multidirectional agility assessments, and postural stability trials conducted on a stabilometric platform. The results clearly demonstrate the highly beneficial effects of OPW training. Significant improvements were observed in key motor abilities, particularly in aerobic endurance, explosive strength, handgrip isometric strength, and overall physical fitness. Most students also exhibited favourable changes in body composition, including increased muscle mass and reduced body fat percentage, with these effects being especially pronounced among male participants. Female participants, on the other hand, showed marked progress in coordination and balance, further confirming the overall effectiveness of the program. The most aronounced improvement was observed between the first and second measurement points, suggesting a rapid physiological adaptation to the intensified training regimen. By the time of the final assessment, the results indicated a stabilization of these gains, while maintaining a consistently high level of physical fitness. In conclusion, the targeted training implemented within uniformed classes constitutes an effective means of developing motor abilities of students and may be regarded as a valuable model of physical preparation. The findings obtained in this study offer a compelling rationale for the continued refinement and expansion of OPW programs, as well as for their broader integration into recruitment and preservice training pathways for candidates aspiring to enter uniformed services. Such initiatives have the potential to enhance not only physical readiness but also long-term effectiveness and resilience within future professional service roles.
Variability of Selected Motor Abilities Under the Influence of Targeted Training among uniformed class students
Promotor: dr hab. Paweł Król, prof. UR ; promotor pomocniczy: dr Jarosław Herbert - 177 s.
Keywords: zdolności motoryczne; szkolenie klas mundurowych; motor abilities; uniformed class training